Bastefia Bag (Banana Stem Fiber Tea Bag) as Innovative Tea Bag Environmentally Friendly Non-Microplastic - Andi Keisha Aisyah; Andi Syifanna Rusyidah; Anindyah Azzahrah Rahmadi; Aryati Rajab (ECOTON: Ecological Observation and Wetlands Conservation, 2026)
Microplastics have become a major threat to humans. Indonesians are estimated to consume 15 grams of microplastic per capita per month, equivalent to three ATM cards, one source of which is tea bags. Unknowingly, these tea bags release or produce microplastics, which can become toxic if they pollute the environment. This microplastic waste can be channeled into the ocean through waterways. Researchers conducted a study aimed at determining how to make Bastefia Bag using banana stem fiber as the raw material and its efficiency as a substitute for commercial tea bags. The research method used was an experiment, namely conducting organoleptic tests, comparing Bastefia Bag with ordinary tea bags in terms of solubility in water at 100°C, and biodegradability tests. The results of this study indicate that banana stem fiber is effective as a raw material for Bastefia Bag without altering the function of commercial tea bags.